Prenatal cigarette smoke exposure sensitizes acetaminophen-induced liver injury by modulating miR-34a-5p in male offspring mice - Yang, Daram; Jeong, Hyuneui; Kim, Min-Seok; Oh, Sang-Ik; Lee, Kyuhong; Kim, Jong-Won; Kim, Bumseok (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Cigarette smoke (CS) exacerbates the severity of diseases not only in lungs, but also in systemic organs having no direct contact with smoke. In addition, smoking during pregnancy can have severe health consequences for both the mother and the fetus. Therefore, our aim was to evaluate effects of prenatal exposure to CS on acetaminophen (APAP)-induced acute liver injury (ALI) in offspring. Methods: Female C57BL/6 mice on day 6 of gestation were exposed to mainstream CS (MSCS) at 0, 150, 300, or 600 μg/L for 2 h a day, 5 days a week for 2 weeks using a nose-only exposure system. At four weeks old, male offspring mice were injected intraperitoneally with a single dose of APAP at 300 mg/kg body weight to induce ALI. Results: Maternal MSCS exposure significantly amplified pathological effects associated with ALI as evidenced by elevated serum alanine aminotransferase levels, increased hepatocellular apoptosis, higher oxidative stress, and increased inflammation. Interestingly, maternal MSCS exposure reduced microRNA (miR)-34a-5p expression in livers of offspring. Moreover, treatment with a miR-34a-5p mimic significantly mitigated the severity of APAP-induced hepatotoxicity. Overexpression of miR-34a-5p completely abrogated adverse effects of maternal MSCS exposure in offspring with ALI. Mechanistically, miR-34a-5p significantly decreased expression levels of hepatocyte nuclear factor 4 alpha, leading to down-regulated expression of cytochrome P450 (CYP)1A2 and CYP3A11. Discussion: Prenatal exposure to MSCS can alter the expression of miRNAs, even in the absence of additional MSCS exposure, potentially increasing susceptibility to APAP exposure in male offspring mice.